Growth Prospects Through Innovation Systems for Utilising Mineral Wastes in Production (The Australasian Institute of Mining and Metallurgy, 2002)
Mineral formations, accumulated during technogenic activities greatly influence an economic and ecological situation in the Kola North. On the one hand, the dumps from extraction of mineral resources, tailing ponds of beneficating plants, ash dumps, wastes of metallurgical and mechanical engineering productions destroy the regionÆs environment and require taking certain measures and costs to bury or protect from weathering, oxidation, etc. On the other hand, technogenic mineral formations contain a lot of valuable scarce components. The amount of solid wastes increases annually, causing damage to ecology and economy. Researches conducted in recent years showed a possibility and economic expediency of comprehensive processing of wastes from different enterprises in Murmansk region and their use for production of new competitive commodity output, possessing high consumer properties. Thus, involving mineral wastes from Khibiny apatite deposits into hydrometallurgical industrial processing provides the basis for setting up a large beneficating-metallurgical complex. In this case ores and wastes from other deposits on the Kola Peninsula, containing titanium, rare, rare-earth and other valuable elements, may be involved into processing. Establishing such a complex will allow to organise a deep processing of natural resources, utilise some production wastes, improve ecological security and supply production with competitive output. Expanding the complex implies not only involving new mineral raw material into processing, but mainly deepening raw material processing, maximum utilisation of local natural resources and obtaining a wider variety of prime products.